Transmissão de conteúdos religiosos: o diálogo de catequistas com crianças e jovens surdo em Parnaíba - PI - Nascimento, Patricia Gabriela Batista do (2013)
The present study investigated how is the transmission of religious content for children and young deaf people, since this is the spread of the word of God, to an audience that is diverse, using Brazilian Sign Language (LIBRAS) for their communication. Because it is a little known study within our county as identified by our research, the literature became sparse, but the study has achieved the goal of locating in which religious entity in the City of Parnaíba (Piauí) is used LIBRAS as a way to avoid evasion of the deaf within this context. The recommendations outlined in the literature emphasize that interpreters must constantly seek alternatives, such as offering the use of LIBRAS for the deaf can understand the biblical messages that may be seeking to know God, and our religious environments may offer a better quality of understanding of the doctrine Christian.